Contrasting effects of long term versus short-term nitrogen addition on photosynthesis and respiration in the Arctic - van de Weg, M.J.; Shaver, G.R.; Salmon, V.G (Plant Ecology, 2013)
We examined the effects of short (<1-4 years) and long-term (22 years) nitrogen (N) and/or phosphorus (P) addition on the foliar CO